Association of mycophenolate and azathioprine use with cognitive function in systemic lupus. (22nd September 2022) - Dobrowolski, Chrisanna; McGinley, John; Fazzari, Melissa; Su, Jiandong; Bingham, Kathleen S; Anderson, Nicole; Ruttan, Lesley; Beaton, Dorcas E; Wither, Joan E; Tartaglia, Maria Carmela; Kakvan, Mahta; Bonilla, Dennisse; et al.
Abstract: Objectives: Cognitive dysfunction (CD) is a common manifestation of SLE that can have detrimental consequences for those affected. To date, no treatments have been approved for SLE-CD. This study aims to assess the association of azathioprine (AZA) and mycophenolate (MMF) use with SLE-CD, given that these medications have demonstrated neuroprotective qualities in prior studies. Methods: Consecutive adult SLE patients presenting to a single healthcare center were considered for participation. The ACR neuropsychological battery for SLE was administered to consenting patients at 0, 6 and 12 months. Scores were compared with age- and sex-matched controls. Primary outcome was CD, defined as a z -score ≤−1.5 in two or more cognitive domains. Mixed-effects logistic regression models were constructed to estimate the odds of CD with respect to AZA and MMF use. Results: A total of 300 participants representing 676 patient visits completed the study; 114 (38%) met criteria for CD at baseline. The cumulative AZA dose (g/kg) was associated with reduced odds of CD [odds ratio (OR) 0.76 (95% CI 0.58, 0.98), P = 0.04]. Years of AZA treatment was also associated with reduced odds of CD [OR 0.72 (95% CI 0.54, 0.97), P = 0.03]. MMF use was not associated with CD. Conclusion: AZA use was associated with significantly lower odds of SLE-CD, while MMF use was not. Additional studies are warranted to further investigate the relationship of AZA and SLE-CD.